Exploring Elementary School Readiness for Implementing Deep Learning Technology in Digital Education - Ria Norfika Yuliandari (International Journal of Elementary Education, 2025)
This study addresses the challenge of unequal technology access in rural elementary schools and the lack of pedagogical preparedness in integrating intelligent technologies, such as deep learning, into digital learning environments. The research aims to evaluate the readiness of elementary schools to adopt technology-driven digital learning. It focuses on teachers’ skills, students’ access to devices and the internet, and the development of a digital culture within schools. A qualitative case study approach was used. The research participants included 4 school principals, 8 teachers (4 classroom teachers and 4 ICT teachers),  Data were gathered through in-depth interviews, participatory observations, and documentation, and then analyzed thematically. The results show that digital learning readiness involves not only technical capabilities but also pedagogical preparedness shaped by social dynamics and local limitations. Disparities in device access, limited digital literacy among teachers, and lack of family support were identified as key challenges. The study recommends strategies tailored to specific contexts for building digital capacity and provides a replicable framework to evaluate elementary schools' readiness to foster an inclusive digital learning environment.